Плавність руху автобусів у взаємозв’язку з характеристиками підвіски та сидінь - Бур’ян, Михайло Володимирович (Національний університет "Львівська політехніка", 2020)
У дисертаційній роботі розв’язано науково-практичне завдання оцінки та оптимізації рівня вібронавантаження, що діють на пасажирів автобуса з умов плавності руху . Зокрема, створена імітаційна модель, завдяки якій можна ще на стадії проектування оцінити значення вібронавантажень, що діють на пасажирів, тобто справляти безпосередній вплив на комфортність перевезень. Проведені імітаційні моделювання з кількома типами задньої підвіски за різних рівнів завантаження, з визначенням кількісних значень в характерних місцях автобуса. Моделювання проведено з імітацією дороги ІІ категорії, а також під час переїзду засобу примусового сповільнення швидкості. Проведені експериментальні дослідження аналогічних автобусів на аналогічних типах покриття, після співставлення з результатами імітаційного моделювання, засвідчили адекватність моделі. Результати проведених досліджень є основою для формування нового державного стандарту - ДСТУ «Колісні транспортні засоби. Плавність руху. Методи проведення випробувань та оцінка вібронавантажень/комфортності пасажирських перевезень». В диссертационной работе решена научно-практическая задача оценки и оптимизации уровня вибронагруженности, что воздействует на пассажиров автобуса по условиям плавности хода. В частности, создана имитационная модель, посредством которой еще на этапе проектирования можно оценить уровни вибронагруженности, что воздействуют на пассажиров – т.е. производить непосредственное влияние на комфортность перевозок. Проведены имитационные моделирования с разными типами задней подвески при разных уровнях загруженности, с определением количественных значений в характерных местах автобуса. Моделирование проведено с имитацией дороги ІІкатегории, а также при переезде порогового препятствия - средства принудительного снижения скорости. Проведенные экспериментальные исследования аналогичных автобусов на аналогичных типах покрытия, после сравнения, подтвердили адекватность модели. Результаты проведенных исследований стали основой для формирования нового государственного стандарта ДСТУ «Колесные транспортные средства. Плавность хода. Методы проведения испытаний и оценка вибронагруженности/комфортности пасажирских перевозок». Dissertation solves scientific and practical task of assessing and optimizing the level of vibration load acting on the bus passengers in depends of the smooth traffic conditions, class of the bus purpose, and statistical generalization of the average duration of passengers trips. In particular, based on mathematical model, which consist of nine well known from theory equations, was created Matlab Simulink simulational model which allows to detrminate level of vibrational loads that affects on bus passangers at the stage of bus designing. Such approach allows to imapct directly on the ride comfort of passanger transportation. Specific places in the bus salon - near the driver at front overhang, at the middle of the bus base and at the rear overhang was chosen to determine vibration loads. Another characteristic feature of the model consist in usage of equivalent function of statistical distribution to describe the real road profile. In such way quantitative values of vibrational loads in specific places in the bus salon for different types of rear suspension at different load levels was determined by using created simulation model. Obtained results were processed by methods of mathematical statistics and distributed by octave bands for the possibility of comparative estimation of RMS values of vibration loads. According to the modeling results were received and implemented in the project practice recommendations for the selection of the type and characteristics of the suspension and passenger seats in depens on the class of purpose of the bus (urban, local and intercity transportation). Also experimental road test were conducted for the similar buses on the appropriate types of road coverage, after comparison with the results of simulation, showed the adequacy of the model. For those test was created modern set of measuring equipment for simultaneous assessment of vibration loads on passengers from 3 characteristic areas of the bus salon as well as describbed method of measurements and statistic processing of results with delimitation of frequency ranges. The results of those research are the basis for the creating of a new state standard - "Wheeled vehicles.. Test methods and assessment of vibration loads/comfort of passenger traffic".
Плавность хода автобусов во взаимосвязи с характеристиками подвески и сидений
Ride comfort of buses in relation to the characteristics of the suspension and seats
Keywords: автобус; півдіска; сидіння; вібронавантаження; віброприскорення; плавність руху; комфортність руху; автобус; подвеска; сидения; вибронагруженность; виброускорения; плавность хода; комфортность перевозок; bus; suspension; seats; vibration loading; vibration acceleration; ride comfort; smoothness of movement; comfort of movement; 629.34